Azo-bridged covalent porphyrinic polymers (Azo-CPPs): synthesis and CO2 capture properties. Issue 117 (11th November 2015) - Tao, Liming; Niu, Fang; Zhang, Di; Liu, Jingang; Wang, Tingmei; Wang, Qihua
Abstract : "N2 -phobic" azo and porhpyrinic groups leading to high CO2 /N2 selectivity at high temperature. Abstract : A series of azo-bridged, aromatic, nitrogen-rich, microporous covalent porphyrinic polymers (Azo-CPPs) were synthesized through a metal catalyst-free direct coupling of a kind of tetranitro building block, 4NO2 TPP, and several diamine or tetraamine compounds, under basic conditions. The Azo-CPPs were all amorphous and exhibited surface areas between 197 to 591 m 2 g −1 . The effect of building blocks on the pore properties was discussed. Meanwhile, the capacity of adsorption of CO2 for all the Azo-CPPs was studied and the CO2 uptake capacity was between 7.36% and 9.22% at 273 K and 1.10 bar. The CO2 /N2 selectivities were measured between 27.4–53.9 at 273 K and 31.2–107.8 at 303 K, respectively, showing an increase in selectivity with increasing temperature.